Model-based position tracking control of a hose-connected hydraulic lifting system. (March 2017) - Hou, Jiaoyi; Zhang, Zengmeng; Ning, Dayong; Gong, Yongjun
Abstract: High-pressure rubber hose is normally used to connect the control valves and actuators of hydraulic systems and thus lower their natural frequency. PID control is preferred in industrial hydraulic systems as it has many advantages over other controls. However, the low natural frequency of hose-connected systems limits the performance of PID control. In this paper, a hose-connected hydraulic lifting test rig is presented and the mathematical model of the system is proposed. Valve compensation strategy and hose compensation strategy are designed based respectively on the flow characteristic of the proportional valve and the mathematical model of the hose. Comparative experiments with typical desired trajectories are carried out in the test rig. Results show that both the compensation strategies are effective in improving the tracking accuracy.